2009
DOI: 10.5539/ijef.v1n2p185
|View full text |Cite
|
Sign up to set email alerts
|

The Research of Promoting the Chinese Banking Industry Core Competitiveness under the Financial Globalization Background

Abstract: Along with the Chinese financial market unceasing opening, the financial globalization tendency develops thoroughly, various countries financial market relation is closer, the internationalization degree enhances day by day. The financial innovation and the comprehensive management tendency develop unceasingly, between various professions seeps mutually. The international finance competition is more and more intense; the capital interstate flowing scale expands unceasingly, the element of certainty increases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As Bank of China holds a large amount of foreign currency assets, its earnings are significantly affected by foreign economic conditions. Ma J.T et al (2009) showed it need to continuously improve the risk management system and maintain adequate risk resilience [5].…”
Section: Income Statement Analysismentioning
confidence: 99%
“…As Bank of China holds a large amount of foreign currency assets, its earnings are significantly affected by foreign economic conditions. Ma J.T et al (2009) showed it need to continuously improve the risk management system and maintain adequate risk resilience [5].…”
Section: Income Statement Analysismentioning
confidence: 99%
“…State-owned banks generally perceive SMEs to be high-risk, low-return clients. In general, they prefer lending to large clients such as China's state-owned enterprises (SOEs) and big private corporations, to assure repayment of loans and good relationships with increasingly influential figures in China's political system (Ma & Sun, 2009). In recent years, state-owned banks have been facing more challenges than ever before:…”
Section: Case Study 2: C Bank's Two-layer Modelmentioning
confidence: 99%